Socio-Philosophical Foundations of Constructing An Enlightened Society In The Jadid Intellectual Heritage - Farxodjonova Nodira Farxodjon qizi (Academicia Globe: Inderscience Research, 2026)
This article examines the socio-philosophical foundations of forming an enlightened society and creating a new spiritual space within the spiritual heritage of the Jadids. It reveals the views of Jadid thinkers on the harmonization of national and universal values, the role of education and upbringing in societal development, as well as issues related to spiritual renewal and the transformation of social consciousness. Furthermore, the study substantiates the methodological significance of Jadid ideas in shaping a modern spiritual space and civil society